The early history of glaucoma: the glaucous eye (800 BC to 1050 AD) - Leffler CT (Dove Medical Press, 2015)
Christopher T Leffler,1 Stephen G Schwartz,2 Tamer M Hadi,3 Ali Salman,1 Vivek Vasuki1 1Department of Ophthalmology, Virginia Commonwealth University, Richmond, VA, USA; 2Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Naples, FL, USA; 3Graduate School of Medicine, University of Tennessee Medical Center at Knoxville, TN, USA Abstract: To the ancient Greeks, glaukos occasionally described diseased eyes, but more typically described healthy irides, which were glaucous (light blue, gray, or green). During the Hippocratic period, a pathologic glaukos pupil indicated a media opacity that was not dark. Although not emphasized by present-day ophthalmologists, the pupil in acute angle closure may appear somewhat green, as the mid-dilated pupil exposes the cataractous lens. The ancient Greeks would probably have described a (normal) green iris or (diseased) green pupil as glaukos. During the early Common Era, eye pain, a glaucous hue, pupil irregularities, and absence of light perception indicated a poor prognosis with couching. Galen associated the glaucous hue with a large, anterior, or hard crystalline lens. Medieval Arabic authors translated glaukos as zarqaa, which also commonly described light irides. Ibn Sina (otherwise known as Avicenna) wrote that the zarqaa hue could occur due to anterior prominence of the lens and could occur in an acquired manner. The disease defined by the glaucous pupil in antiquity is ultimately indeterminate, as the complete syndrome of acute angle closure was not described. Nonetheless, it is intriguing that the glaucous pupil connoted a poor prognosis, and came to be associated with a large, anterior, or hard crystalline lens. Keywords: glaucoma, history of ophthalmology, couching